Cognitive dysfunction in bipolar disorder and schizophrenia: a systematic review of meta-analyses - Bortolato B (Dove Medical Press, 2015)
Beatrice Bortolato,1 Kamilla W Miskowiak,2 Cristiano A Köhler,3 Eduard Vieta,4 André F Carvalho3 1Department of Mental Health, ULSS 10 “Veneto Orientale”, Venice, Italy; 2Psychiatric Centre Copenhagen, Copenhagen University Hospital, Rigshospitalet, Copenhagen, Denmark; 3Translational Psychiatry Research Group and Department of Clinical Medicine, Faculty of Medicine, Federal University of Ceará, Fortaleza, CE, Brazil; 4Bipolar Disorders Program, Institute of Neuroscience, Hospital Clínic Barcelona, IDIBAPS, CIBERSAM, University of Barcelona, Catalonia, Spain Abstract: Cognitive impairment is a core feature of schizophrenia (SZ) and bipolar disorder (BD). A neurocognitive profile characterized by widespread cognitive deficits across multiple domains in the context of substantial intellectual impairment, which appears to antedate illness onset, is a replicated finding in SZ. There is no specific neuropsychological signature that can facilitate the diagnostic differentiation of SZ and BD, notwithstanding, neuropsychological deficits appear more severe in SZ. The literature in this field has provided contradictory results due to methodological differences across studies. Meta-analytic techniques may offer an opportunity to synthesize findings and to control for potential sources of heterogeneity. Here, we performed a systematic review of meta-analyses of neuropsychological findings in SZ and BD. While there is no conclusive evidence for progressive cognitive deterioration in either SZ or BD, some findings point to more severe cognitive deficits in patients with early illness onset across both disorders. A compromised pattern of cognitive functioning in individuals at familiar and/or clinical risk to psychosis as well as in first-degree relatives of BD patients suggests that early neurodevelopmental factors may play a role in the emergence of cognitive deficits in both disorders. Premorbid intellectual impairment in SZ and at least in a subgroup of patients with BD may be related to a shared genetically determined influence on neurodevelopment. Keywords: schizophrenia, bipolar disorder, psychosis, neuropsychological tests, cognition, meta-analysis, psychiatry